2016
DOI: 10.16986/huje.2016015387
|View full text |Cite
|
Sign up to set email alerts
|

Cinsiyetin Akademik Erteleme Üzerindeki Etkisi: Meta-Analiz

Abstract: ÖZ:Bu meta-analiz çalışmasında cinsiyetin akademik erteleme üzerindeki üzerindeki etkisi test edilmiştir. Öncelikle literatür taraması yapılarak ilgili yayınlar bir havuzda toplanmıştır (n=97). Araştırmacılar tarafından belirlenen ölçütler doğrultusunda 25 çalışmanın analize dahil edilmesine karar verilmiştir. Rassal etki modeli kullanılarak yapılan analiz sonuçları, cinsiyetin akademik erteleme üzerinde düşük düzeyde anlamlı etkisinin olduğunu göstermektedir (f=25, d= .25, p<.001, SEd= .05). Çalışmada araştır… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As a result of biased beliefs and expectations that they would be successful without effort with their innate abilities, boys tend to delay their academic tasks more often (Heyder & Kessels, 2017; Muntoni & Retelsdorf, 2018). Girls who are exposed to a certain degree of implicit or explicit social pressure do not want their failures to be seen in public, so they act responsibly, which may be one of the reasons for gender differences in AP (Cikrikci & Erzen, 2016). Considering all these results, it can be said that PSU and AP are affected by cultural and social norms and there are many reasons behind the differences between genders in terms of PSU and AP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of biased beliefs and expectations that they would be successful without effort with their innate abilities, boys tend to delay their academic tasks more often (Heyder & Kessels, 2017; Muntoni & Retelsdorf, 2018). Girls who are exposed to a certain degree of implicit or explicit social pressure do not want their failures to be seen in public, so they act responsibly, which may be one of the reasons for gender differences in AP (Cikrikci & Erzen, 2016). Considering all these results, it can be said that PSU and AP are affected by cultural and social norms and there are many reasons behind the differences between genders in terms of PSU and AP.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are more studies stating that boys constitute a risk group for AP and that boys' AP levels are higher than girls' (Özer et al, 2009; Zarick & Stonebraker, 2009). Indeed, meta‐analysis studies conducted by researchers such as Steel (2007) and Cikrikci and Erzen (2016) revealed that boys had higher levels of AP. This may be due to the reflections in academic environments of stereotypical beliefs or prejudices that are supposed to be gender‐specific (Schunk & Pajares, 2002).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Araştırma sonucuna göre öğrencilerin cinsiyetleri ile akademik erteleme davranışları arasında anlamlı farklılık olduğu, erkek öğrencilerin daha fazla erteleme davranışına sahip olduğu tespit edilmiştir. Literatürde araştırma sonucuyla benzerlik gösteren çalışmalar mevcuttur Akdamar ve Kızılkaya, 2022;Albursan vd., 2022;Balkıs ve Duru, 2017;Balkıs vd., 2006;Çelikkaleli ve Evin-Akbay, 2013;Çikrıkci ve Erzen, 2016;Demir ve Kösterelioğlu, 2015;Durdu, 2019;Elhatip, 2018;Eravcı-Özcan, 2020;Erdoğan, 2016;Khan vd. 2014;Lu vd., 2022;Martín-Puga vd., 2022;Pala vd., 2011;Saddler ve Sacks, 1993;Tezer vd., 2020;Uzun-Özer vd., 2009;Uzun-Özer ve Saçkes, 2011;Ying ve Lv, 2012;Zakeri vd., 2013).…”
Section: Tartişma Ve Sonuçunclassified
“…Diğer taraftan ortaokul kademesinde akademik erteleme konusunda yapılan çalışmaların sayıca az olmasından yola çıkarak Durdu, 2019;Eravcı-Özcan, 2022;Kalia ve Yadav, 2014;, ortaokul öğrencilerinin akademik erteleme davranışlarıyla ilgili öznel bakış açılarının ortaya çıkarılmasının literatüre katkı sağlayacağı ve erteleme davranışlarının önlenmesinde ve azaltılmasında iyileştirici çalışmaların yapılması adına yol göstereceği düşünülmektedir. Literatürdeki çalışmalarda, akademik ertelemenin cinsiyet (Albursan vd., 2022;Balkıs vd., 2006, Çikrıkci ve Erzen, 2016Pala vd., 2011;, internet kullanma süresi , akademik başarı (Akdamar ve Kızılkaya, 2022;Akinsola vd., 2007;Duru ve Balkıs, 2014;Owens ve Newbegin, 2000;, sınıf seviyesi Yardım ve Engin, 2022), anne-baba eğitim düzeyi değişkenleriyle ilişkili olmasından hareket edilerek araştırmanın amacı, "öğrencilerin akademik erteleme davranışlarının farklı değişkenlere göre incelenmesi" olarak belirlenmiştir. Araştırmada şu sorulara cevap aranacaktır:…”
Section: Introductionunclassified